Governor’s Award for the design of the book “Tales of Bolshaya Street” - Lisitsina, Yana (project baikal, 2023)
In 2022 the Irkutsk Region Governor’s Award for the creative work in the field of culture and art was given to the writer Yury Baranov and the artists Vasily Lisitsin and Yana Lisitsina for their regional educational publishing project “The Tales of Bolshaya Street”. The article reveals the content of the book and describes the concept of illustrative approach.